Cardiac activity monitor with cathode ray tube - Zarco, J.; Calderon, J.; Meneses, I.; Brusi, H. (Revista Mexicana de Ingenieria Biomedica, 2018)
We present a monitor of heart rate (HR) and electrocardiogram (ECG) represented in a TV tube. The device allows detecting ECG in the usual branches. It uses differential amplifiers with input impedance greater than 2.4 MOhms and common mode rejection greater than 80 dR. Its bandwidth is 0.05 to 100 Hz. The ECG is digitized and stored in memory for presentation in two beams with a 25 or 25 mm / s sweep. One of these strokes can be frozen for continuous analysis. The QRS is used to calculate the HR beat by beat, the result displayed on the screen along with the numbers represent the minimum and maximum HR to activate the audible alarm. Everything is controlled by a microprocessor.